2015
DOI: 10.2139/ssrn.2591988
|View full text |Cite
|
Sign up to set email alerts
|

Social License to Operate: Hydraulic Fracturing-Related Challenges Facing the Oil & Gas Industry

Abstract: The crossroads of urban development and improved technology allowing oil and gas development in new areas can result in contentious community issues. The debate over one of the improved technologies-i.e., hydraulic fracturing-can be highly emotional. Consequently, industry must address community issues, earning trust and therefore a "social license to operate." This paper provides fundamental knowledge of the social license to operate concept, validates its application to the oil and gas industry, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Finally, it may also be useful to more closely examine how SLO is realised under different legislative and regulatory frameworks. While a detailed examination of the legislative frameworks of Australia, China, and Chile was beyond the immediate scope of this paper, there is already a growing interest in exploring the relationship between legislation and social licence (e.g., Smith and Richards, 2015).…”
Section: Reflection On Contextual Differences For Mining Industry Actorsmentioning
confidence: 99%
“…Finally, it may also be useful to more closely examine how SLO is realised under different legislative and regulatory frameworks. While a detailed examination of the legislative frameworks of Australia, China, and Chile was beyond the immediate scope of this paper, there is already a growing interest in exploring the relationship between legislation and social licence (e.g., Smith and Richards, 2015).…”
Section: Reflection On Contextual Differences For Mining Industry Actorsmentioning
confidence: 99%
“…In the context of Shale Gas, notably in North America where there has been a rapid expansion in hydraulic fracturing activities, studies have identified factors which have contributed to a problematic SLO. For instance a historical lack of trust with the industries involved has be found to present a barrier to establishing engagement (Smith and Richards, 2015); this disconnect between stakeholders and communities combined with issues of transparency and lack of enforcement of regulations have been identified as making it particularly challenging to build a SLO (House 2013). An analysis of the print media has also highlighted how concerns and issues vary between regions and over time, suggesting that policies and strategies must be adapted to the specific time and context, stressing the importance of cultural and social concerns in addition to technical or economic risks (Gehman et al, 2016).…”
Section: Elements Of a Social Licencementioning
confidence: 99%
“…Such engagement could promote better decision making, stimulate community trust, and ultimately reduce negative impacts by increasing accountability, which in turn deters negligent practices by act or omission [139]. A key requirement for successful community engagement is the ability to disclose to the public all relevant information regarding baseline data before hydraulic fracturing activities commence, the permitting processes, and all data on operational impacts gathered throughout the lifetime of shale resource exploitation projects [140].…”
Section: Community Engagement Recommendationsmentioning
confidence: 99%